The developing of students’ thinking in the process of studying (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article deals with linguistic and didactic problems of developing students’ thinking in the process of studying grammar. The peculiarities of forming grammar notions on the lessons of the Ukrainian language. The author gives the examples of assignments aimed at developing logical and abstract thinking of pupils.
Keywords: developing of thinking; studying grammar; logic thinking; abstract thinking